👤


1. Efectuați: a) [-3²+(-3)³-(-3)+(-2)×(5-7)]: (-43); b) {(-2)×[(-2)³+5]: 2-(4-8)}×(-2)+[6-(-2)³


Răspuns :

a) [ - 3 la puterea 2 + ( - 3) la puterea 2 - ( - 3) + (-2) × (5-7)

= (-3)×(-3) + (-3) × (-3) - (-3) + ( - 2) × ( 5-7)

= 9 + 9 - 5 × ( - 2)

= 18 + 10 = 28

b) [( - 2) × ( - 2) la puterea 3 + 5] : 2 - (4-8)} × ( - 2) + [ 6 - ( - 2) la puterea 3

= [(-2) × ( - 2)× (-2)×(-2) + 5] : 12 × (-2) + [ 6 - ( - 2)

= [(-2) × ( - 8) +5] : 12 × ( - 2) + [ 6 - (-2)

= (16 +5) : 12 × ( - 2) + [ 6- ( - 2)

= 21 : 12 × (-2) + 8

= 4,5